2021
DOI: 10.1093/ofid/ofab463
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Viremia Is Associated With Cumulative Adherence to Antiretroviral Therapy in Persons With HIV

Abstract: The drivers of low-level viremia (LLV) between 20-200 copies/mL remain unclear. In 1,042 person-visits from 497 persons with HIV on TDF-containing ART, the association between LLV and cumulative antiretroviral adherence (quantified using tenofovir diphosphate (TFV-DP) in dried blood spots) was assessed. Lower TFV-DP levels were associated with higher odds of LLV. As TFV-DP (fmol/punch) categories decreased from >1,650 to 800-1,650; 800-1,650 to <800; and >1,650 to <800, the adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…However, our observation of emergent DRMs during LLV episodes implies that LLV, even in this low range, could be associated with ongoing replication, at least in some individuals. In this context, suboptimal adherence could act as a confounder for the relationship between LLV and VF [ 32 ], as could pre-ART DRM [ 29 ]; the lack of adherence data is a limitation of our study in this respect. Considering the possibility of confounding, here exemplified by reservoir size, adherence, and pre-ART resistance, a causal relationship between LLV and VF cannot be established from our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, our observation of emergent DRMs during LLV episodes implies that LLV, even in this low range, could be associated with ongoing replication, at least in some individuals. In this context, suboptimal adherence could act as a confounder for the relationship between LLV and VF [ 32 ], as could pre-ART DRM [ 29 ]; the lack of adherence data is a limitation of our study in this respect. Considering the possibility of confounding, here exemplified by reservoir size, adherence, and pre-ART resistance, a causal relationship between LLV and VF cannot be established from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus-associated chronic inflammation and immune activation play a key role, driven in part by ongoing low-level viral replication at reservoir sites despite ART-induced virologic suppression [ 10 , 11 ]. Furthermore, ART-treated PWH may experience intermittent viral nonsuppression [ 12 , 13 , 14 ], which may further heighten the inflammatory state that exists among PWH with controlled HIV, potentially contributing to deleterious end-organ effects [ 11 , 15 ]. At any given HIV-1 ribonucleic acid viral load (VL), women have greater immune activation and higher systemic levels of inflammatory biomarkers than men [ 16 ], possibly impacting differential NACM risk by sex observed in PWH [ 17 ].…”
mentioning
confidence: 99%
“…These findings were compatible with those of Castillo-Mancilla et al, showing a possible relationship between treatment adherence and LLV. 22 We found that the integrase inhibitor was not a predictor of a mean CD4 + cell count ≥500 cells/μL. Changing the ART regimen might not be helpful in the setting of LLV.…”
Section: Discussionmentioning
confidence: 60%
“…These findings were compatible with those of Castillo-Mancilla et al, showing a possible relationship between treatment adherence and LLV. 22…”
Section: Discussionmentioning
confidence: 99%